Correlation Between Chlorophyll Degradation and the Amount of Heavy Metals Found in Pseudevernia furfuracea in Kayseri (Turkey) - Akbulut, Gamze; Duman, Fatih; Yildiz, Atila; Demirezen, Dilek; Islek, Cemil; Altuner, Ergin Murat; Aksoy, Ahmet (Cevre Koruma ve Arastirma Vakfi, 2011)
Air pollution and associated heavy metal pollution, is an important environmental problem. One of the methods used to monitor heavy pollution in the air is the method of transplanting lichen samples by the "bag technique". In this study, Pseudevernia furfuracea was used as a bioindicator to determine the heavy metal level of air pollution heavy metal level in Kayseri and to generate an air pollution map of the city. The lichen samples were collected from the Yaprakli Mountains in Cankiri in 2002 and transplanted to 10 different stations in Kayseri. Lichen samples were re-collected at two different periods in three month intervals. Inductively coupled plasma (ICP) spectrometry was used to identify the heavy metals, such as Cu, Cd, Mn, Ni, Pb and Zn in the lichen samples. The chlorophyll a and b contents were determined by using the DMSO method. With these values chlorophyll a+b, a/b and b/a were also calculated.
Keywords: 13. Climate action; 11. Sustainability; 6. Clean water